Tricuspid annular dimensions in patients with severe mitral regurgitation without severe tricuspid regurgitation - Kapadia, Sohum (Cardiovasc Diagn Ther, 2021)
BACKGROUND: Concomitant TV repair during mitral valve (MV) surgery based on tricuspid valve annulus (TVA) dilation, rather than the degree of tricuspid regurgitation (TR), is beneficial and supported by the valve guidelines. We sought to determine TVA geometry and dimensions in controls and assess the changes that occur in patients with severe primary (PMR) and secondary (SMR) mitral regurgitation without TR. METHODS: We analyzed cardiac computed tomographic angiography (CCTA) of 125 consecutive subjects: 50 controls with normal coronary CCTA and no valvular dysfunction, 50 PMR patients referred for robotic repair, and 25 SMR patients referred for transcatheter therapy. Patients with >2+ TR on echocardiography were excluded. Annular measurements were performed using dedicated software and compared. Correlations and determinants of TVA dimensions were analyzed. RESULTS: Patients with SMR were older and had significantly more comorbidities. In controls, the TVA was larger and more planar and eccentric compared to the MV annulus (all P<0.01). Dimensions of both annuli correlated significantly (r≥0.5; P<0.001 for all dimensions) in controls and patients with severe MR. In both PMR and SMR, the TVA enlarged in all dimensions (P<0.01) with a trend towards becoming more circular. On multivariable regression, the MV annular area was the primary determinant of the TVA area (adjusted β=0.430, P<0.001). CONCLUSIONS: Substantial changes in TVA dimensions are encountered in patients with severe MR even in the absence of severe TR such that TVA and MVA dimensions remain correlated. Close attention to the TVA in patients with severe MR is warranted.